PENGEMBANGAN DESA SIAGA DONOR DARAH MELALUI PROGRAM PEMERIKSAAN DAN PENDATAAN GOLONGAN DARAH WARGA DUSUN MANGGONG, KEPUHARJO, CANGKRINGAN, SLEMAN - Gravinda Widyaswara; Wiwit Sepvianti; Aulia Rahman; Kumara Rahmawati Zain; Arif Tirtana; Ikrimah Nafilata (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The Allert Village is a village that has a Village Health Post or health professionals who are ready to carry out community empowerment, encourage health-oriented development, and be the first referral center for quality health services for the community and health emergencies in the Village. In moving towards the allert village, it is necessary to study various existing community-based activities such as posyandu, polindes, village medicine post, health fund, and inter-guard preparedness, as a starting point for development towards an allert village. One of the Allert Village programs currently being developed is the Blood Donor Allert Viilage. In this program, village communities are prepared to be responsive in dealing with health problems that require blood donors. The development of the Blood Donor Allert Village was initiated with outreach activities, data collection and examination of the blood group of residents in each hamlet. Data on residents' blood groups is then submitted to village midwives, sub-districts and health centers as a data base for the Blood Donor Allert Village. Blood group data collection for the residents of Manggong, one of the hamlets in Kepuharjo Village, obtained the following results: out of a total of 256 r esidents, 62.50% had their blood type recorded while 37.50% was not. As for the 62.50% of Dusun Manggong residents whose blood type was recorded, 26.87% had blood type A; 28.13% blood type B; 41.25% have blood type O and only 3.75% have blood type AB